A method for controlling edge defects on the surface of 316L stainless steel
By adjusting the composition and process parameters of 316L stainless steel, controlling the residual ferrite content and increasing the ferrite content of the casting billet, the problem of side scale defects in 316L stainless steel during cold rolling was solved, and the product quality and qualification were significantly improved. rate, reducing metal loss.
Patent Information
- Application Number
- CN202411435470.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-15
AI Technical Summary
316L stainless steel is prone to edge scale defects during cold rolling, which affects product quality and pass rate, and increases metal loss for downstream users.
By adjusting the composition of 316L stainless steel, the residual ferrite content is controlled between 4 and 9%, and the cooling water volume and temperature difference are increased in the continuous casting process to increase the actual residual ferrite content of the casting billet. At the same time, the heating temperature and time are controlled through the hot rolling process to ensure the transformation of ferrite, and the total pressure reduction rate is increased during the rough rolling process to reduce the uneven deformation of the two phases during the finishing rolling process.
The incidence of scale-fold defects on the edge surface of the 316L stainless steel coil has been effectively reduced, from the original 9.28% to less than 1%, improving the product quality and qualification rate and reducing metal losses for downstream users.
Smart Images

Figure CN118932243B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of stainless steel, and in particular to a method for controlling edge defects on the surface of 316L stainless steel. Background Art
[0002] 316L is an austenitic steel. 2~3% Mo is added to 304 steel. It has excellent pitting corrosion resistance, high temperature resistance, creep resistance and good welding performance. Its C content is lower than that of conventional 304, and it has excellent intergranular corrosion resistance and can be used under more severe corrosion conditions. Due to the high alloy content, the harmful trace element S is required to be high. During the solidification process of austenitic stainless steel, sulfur enrichment between dendrites will weaken the intergranular bonding force and cause a decrease in plasticity. It mainly exists in the material in the form of MnS and FeS. FeS has a low melting point (1190°C) and is also easy to exist in liquid form on the grain boundary during continuous casting solidification and heating, resulting in a decrease in plasticity and the occurrence of cracks. Since the solubility of S in ferrite is much higher than that in austenite, in order to reduce the risk brought by S, the design idea of the composition is to adjust the alloying elements of Ni and Cr equivalents to ensure that the content of residual ferrite in the ingot is between 4 and 9%, dg = [(Cr+Mo+1.5Si+0.5Nb+2Ti+18) / (Ni+30C+30N+0.5Mn+36) +0.262]×161-161.
[0003] The microstructure of 316L is composed of austenite and trace ferrite. If the ferrite content is not well controlled, excessive ferrite will lead to the inability to eliminate it during the heating and rough rolling process, and two-phase rolling will occur during the finishing rolling process. Uneven deformation of the two phases can easily lead to cracks, and scale defects will appear in the subsequent process; if there is too little ferrite, harmful trace elements will segregate at the grain boundaries in the form of low-melting-point compounds, causing cracks.
[0004] Chinese patent publication number CN112342454A discloses “A 316L stainless steel and its preparation method”, which mentions that the scale defects on both sides of the edge are controlled by controlling the S content.
[0005] In the study of scale defects and precipitation behavior of BN1TL stainless steel, it is mentioned that the main causes of scale defects in austenitic stainless steel are: excessive residual ferrite, inclusion of continuous casting protection slag, precipitation phase and segregation. Summary of the invention
[0006] The main purpose of the present invention is to provide a method for controlling the edge scale defect of 316L stainless steel coil surface, so as to solve the problem that the edge scale defect of 316L steel occurs during the cold rolling process, which has a great influence on the quality and qualified rate of the product, limits the scope of use of the product, and increases the metal loss of downstream users.
[0007] To achieve the above purpose, the technical solution of the present invention is as follows:
[0008] A method for controlling edge defects on the surface of 316L stainless steel comprises the following steps:
[0009] 1) Smelting
[0010] According to the following composition, 316L stainless steel is smelted with the following composition percentages: C: ≤0.03%, Si: 0.4~0.7%, Mn: 1.1~1.4%, P≤0.045%, S: ≤0.003%, Cr: 16.0~17.5%, Ni: 10.0~11.0%, Mo: 2.0~2.2%, Cu: ≤0.30%, N: ≤0.045%, the remainder is Fe and other unavoidable impurities, and the following must be met at the same time: the residual ferrite dg value is between 4~9%,
[0011] dg=
(Cr+Mo+1.5Si+0.5Nb+2Ti+18) / (Ni+30C+30N+0.5Mn+36)+0.262
[0012] 2) Casting
[0013] The continuous casting process is used to cast the ingot, the secondary cooling water volume is 18~30L / s, the temperature difference between the inlet and outlet water of the continuous casting is 4~11℃, and the actual residual ferrite content of the ingot is between 6~10.5%;
[0014] 3) Rolling
[0015] The heating temperature of the ingot is controlled at 1230~1270℃, and the heating time is 180~260min; the total reduction rate of hot rolling and rough rolling is ≥84%, and the relative reduction rate of each pass is 28~32%.
[0016] In the design of the method of the present invention:
[0017] The composition of the stainless steel is controlled as follows:
[0018] Carbon: Carbon is an element that strongly forms and stabilizes austenite. Too much carbon will cause carbide precipitation and reduce intergranular corrosion performance. The present invention controls C: ≤0.03%.
[0019] Silicon: Silicon is a strong ferrite-forming element and is a deoxidizer mainly used in the steelmaking process; the present invention controls Si to 0.4-0.7%.
[0020] Manganese: Manganese is a relatively weak austenite-forming element, which has a strong effect of stabilizing austenite structure and can increase the solubility of nitrogen in austenitic stainless steel. Another important function of manganese is to form MnS, inhibit the harmful effects of sulfur, and improve the high-temperature thermoplasticity of high-chromium-nickel austenitic stainless steel. However, manganese will reduce the corrosion resistance of stainless steel. Therefore, the Mn content of 316L should be appropriately controlled in design. The present invention controls Mn: 1.1~1.4%.
[0021] Chromium: Chromium is a ferrite-forming element and is the main element for making steel stainless and corrosion-resistant. The present invention controls Cr to 16.0-17.5%.
[0022] Nickel: Nickel is an element that strongly forms and stabilizes austenite and can improve cold working properties; the present invention controls Ni to 10.0-11.0%.
[0023] Molybdenum: Mo is the most important element in 316L stainless steel besides chromium and nickel. It is a strong ferrite-forming element and can promote the enrichment of Cr in the passivation film, thereby improving the stability of the stainless steel passivation film. The present invention controls Mo to 2.0-2.2%.
[0024] Copper: Copper can improve the corrosion resistance, mechanical properties, cold forming properties and cutting properties of steel. As the copper content in steel increases, the thermoplasticity of stainless steel decreases. The present invention controls Cu: ≤0.30%.
[0025] Nitrogen: Nitrogen is an element that strongly forms and stabilizes austenite. Nitrogen can replace part of nickel in austenitic stainless steel. The present invention controls N: ≤0.045%.
[0026] Phosphorus and sulfur: harmful elements. The present invention controls P: ≤0.045%, S: ≤0.003%.
[0027] While controlling the above components, it is also necessary to meet the following requirements: the residual ferrite dg value is between 5% and 9%. The solubility of S in ferrite is much higher than that in austenite. In order to reduce the risk brought by S, the composition is designed by adjusting the alloying elements of Ni and Cr equivalents to ensure the residual ferrite content of the ingot dg = (Cr+Mo+1.5Si+0.5Nb+2Ti+18) / (Ni+30C+30N+0.5Mn+36)+0.262]×161-161.
[0028] During the continuous casting process, the secondary cooling water flow rate is controlled at 18~30L / S, and the inlet and outlet water temperature difference is controlled at 4~11℃, so that the actual residual ferrite content of the ingot is between 6~10.5%.
[0029] When the S content in the composition is high, the dg value designed according to the composition cannot dissolve all the S. Therefore, it is necessary to adjust the cooling (water volume and water temperature) in the continuous casting process to increase the actual ferrite content of the ingot to dissolve S, thereby avoiding the risks brought by S.
[0030] In the continuous casting process, as the continuous casting water volume and temperature difference decrease, the high-temperature ferrite precipitation temperature range of the phase diagram calculated by the Therma1~Calc thermodynamic calculation software is 1294~1452℃ (such as Figure 3 As shown in the figure, the cooling speed of the ingot is slow, the residence time in the ferrite precipitation temperature range is long, and the actual amount of residual ferrite precipitation in the ingot increases (as shown in the figure). Figure 7~Figure 9 , Figure 7~Figure 9 The water volume and temperature difference gradually decrease).
[0031] In the hot rolling process, the phase diagram calculated by the Therma1~Calc thermodynamic calculation software shows that the precipitation temperature of ferrite is 1294℃. In order to avoid ferrite precipitation during heating, the heating temperature is controlled below 1294℃.
[0032] At the same time, the ingot samples were taken for simulated heating: different heating temperatures were used to compare the transformation of high-temperature ferrite; as the furnace temperature increased, the ferrite gradually decreased, and after the furnace temperature reached 1245°C, the high-temperature ferrite basically stopped transforming, and the final residual high-temperature ferrite was about 1.6% (such as Figure 4 as shown).
[0033] The slab is placed in a heating furnace for heating, and the heating temperature is controlled at 1230~1270℃, and the heating time is 200~260min. Too high a heating temperature and too long a heating time can easily lead to coarse grains and decreased plasticity, and the occurrence of cracks can lead to the occurrence of scale defects.
[0034] The total reduction rate of hot rolling rough rolling is ≥84%, and the relative reduction rate of each pass is between 28% and 32% (the relative reduction rate of each pass is the ratio of the rolling reduction thickness to the outlet thickness of the previous pass). Increasing the total reduction rate of rough rolling to control ferrite is to provide energy for the transformation of ferrite through the deformation heat generated by deformation.
[0035] When entering the finishing rolling, there is too much residual ferrite. During the finishing rolling process, the austenite and ferrite deform unevenly, resulting in cracks. Through the microscopic analysis of the scale defect by the probe, the defect location is mainly metal oxidation, no sulfide is found, and there is part of ferrite at the crack head, which further shows that the scale defect is the crack oxidation caused by the uneven deformation of the two phases during the steel rolling process (such as Figure 5 , Figure 6 as shown).
[0036] Compared with the prior art, the present invention has the following advantages:
[0037] In the case of excessive residual ferrite, the existing technology controls the occurrence of cracks by controlling harmful trace elements or reducing the ferrite of the ingot.
[0038] The present invention increases residual ferrite during the continuous casting process to dissolve harmful trace elements, and controls the residual ferrite through a subsequent hot rolling process.
[0039] The existing technology has greatly improved the scale fold by controlling the S content, but there is still a certain proportion of scale fold defect degradation (such as Figure 1 as shown).
[0040] The present invention mainly reduces the risk brought by S by increasing the actual residual ferrite in steelmaking continuous casting, and increases the reduction rate in rough rolling to improve the transformation of ferrite, so that the ferrite content of the intermediate billet is below 0.6%. (With the increase of the total reduction rate of rough rolling, the increase of deformation heat promotes the transformation of ferrite, and the ferrite content of the intermediate billet gradually decreases. Figure 2 As shown in the figure, the intermediate billet enters the finishing rolling with lower ferrite to avoid two-phase rolling of the finishing rolling, which not only avoids the risk brought by S but also avoids the scale-break defect caused by uneven deformation of the two phases. The scale-break defect is reduced from the original 9.28% to less than 1% through the control of the present invention.
[0041] The present invention allows a larger amount of sulfur in the steelmaking process, and increases the residual ferrite of the ingot to dissolve the sulfur in the steelmaking process through a continuous casting process, and then increases the transformation of ferrite by controlling the large reduction rate of rough rolling, thereby promoting less ferrite in the finishing rolling process and reducing cracks caused by the uncoordinated deformation of the two phases in the finishing rolling process. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 The relationship between 316L scale defect, S content and Dg value;
[0043] Figure 2 The relationship between the ferrite content of 316L intermediate billet and the total reduction rate of rough rolling;
[0044] Figure 3 The phase diagram of 316L composition calculated by Therma1~Calc thermodynamic calculation software;
[0045] Figure 4 Simulate different heating temperature structures and ferrite contents for 316L ingot;
[0046] Figure 5 This is a photo of the edge fold defect of 316L;
[0047] Figure 6 This is the microscopic cross-section analysis of 316L scale fracture defects;
[0048] Figure 7 Schematic diagram of ferrite distribution on the end surface of 316L ingot (ferrite content 7.3%);
[0049] Figure 8Schematic diagram of ferrite distribution on the end surface of 316L ingot (ferrite content 8.4%);
[0050] Fig. 9 Schematic diagram of ferrite distribution on the end surface of 316L ingot (ferrite content 9.3%);
[0051] Fig.10 The metallographic structure and ferrite content of the intermediate billet of 316L with a total rough rolling reduction of 84% (ferrite content 0.55%);
[0052] Fig.11 The metallographic structure and ferrite content of the intermediate billet of 316L with a total rough rolling reduction of 82% (ferrite content 0.68%);
[0053] Fig.12 The metallographic structure and ferrite content of the intermediate billet of 316L with a total rough rolling reduction of 81% (ferrite content 0.77%);
[0054] Fig.13 The metallographic structure and ferrite content (ferrite content 0.95%) of the intermediate billet of 316L with a total rough rolling reduction of 79%. DETAILED DESCRIPTION
[0055] The present invention will be further described below in conjunction with the embodiments and drawings.
[0056] The composition of the embodiment of the present invention is shown in Table 1, and the balance of the composition includes Fe and other inevitable impurities;
[0057] According to the process control requirements, the embodiment of the present invention tracks the folding of the edges on both sides in 8 comparative examples.
[0058] From Table 2, it can be seen that for Examples 1 to 10, the actual residual ferrite content is relatively high, between 6 and 10.5%, the total reduction ratio of rough rolling is controlled to be ≥84%, and the ferrite of the intermediate billet is within 0.6% without any edge scale defects.
[0059] The actual residual ferrite content of Comparative Examples 1 to 5 is relatively low, below 6%, and the ferrite content is also low when rolling the intermediate billet. Due to the high S content, the residual ferrite is insufficient, and S segregation occurs during the rough rolling process, resulting in cracks.
[0060] In Comparative Examples 5 to 8, the residual ferrite of the ingot was between 6% and 10.5%, the total reduction rates of rough rolling were 79%, 81%, and 82%, respectively, and the ferrite of the intermediate ingot was about 0.95%, 0.77%, and 0.68%, respectively. All of them had scale defects, the reduction rate was too low, the residual ferrite was too much, and the uneven deformation of the two phases led to cracks.
[0061] In summary, the experimental case comparison shows that the residual ferrite content is too low, and FeS appears during the rough rolling process. The rough rolling temperature is higher than the melting point of FeS, resulting in the presence of liquid phase, which causes cracks; as the total rough rolling reduction rate increases, the ferrite content of the intermediate billet gradually decreases (e.g. Figure 10~Figure 13 As shown in the figure), the ratio of scale defects also gradually decreased, indicating that increasing the reduction rate of rough rolling is conducive to the transformation of ferrite and reducing two-phase rolling during the finishing rolling process (the uncoordinated deformation of the two phases can easily lead to the occurrence of cracks).
[0062] Table 3 shows the relationship between the scale defects on both sides of the finished product and the hot rolling and rough rolling deformation in the industrial batch production of 316L stainless steel, with the higher residual ferrite content controlled between 6 and 10.5%. As the deformation increases, the degradation rate of the scale defects becomes lower and lower; this shows that by increasing the residual ferrite of the ingot and then increasing the deformation of the rough rolling to control the ferrite of the intermediate ingot, the scale defects on both sides of the finished product are effectively reduced.
[0063]
[0064]
[0065]
Claims
1. A method for controlling edge defects on the surface of 316L stainless steel, characterized in that: The steps include: 1) Smelting According to the following composition, 316L stainless steel is smelted with the following composition mass percentage: C: ≤0.03%, Si: 0.4~0.7%, Mn: 1.1~1.4%, P≤0.045%, S≤0.003%, Cr: 16.0~17.5%, Ni: 10.0~11.0%, Mo: 2.0~2.2%, Cu: ≤0.30%, N: ≤0.045%, the remainder is Fe and other unavoidable impurities, and it must also meet the following requirements: the residual ferrite dg is between 4~9%, dg=【(Cr+Mo+1.5Si+0.5Nb+2Ti+18) / (Ni+30C+30N+0.5Mn+36)+0.262】×161-161; 2) Casting The continuous casting process is used to cast the ingot, the secondary cooling water volume is 18~30L / s, the temperature difference between the inlet and outlet water of the continuous casting is 4~11℃, and the actual residual ferrite content of the ingot is between 6~10.5%; 3) Rolling The heating temperature of the ingot is controlled at 1230~1270℃, and the heating time is 180~260min; the total reduction rate of hot rolling and rough rolling is ≥84%, and the relative reduction rate of each pass is 28~32%.
Citation Information
Patent Citations
316L stainless steel and preparation method thereof
CN112342454A
Austenite stainless steel and production method thereof
CN103924163A
Nickel-saving high-nitrogen austenitic stainless steel with excellent pitting corrosion resistance and sulfuric acid corrosion resistance and manufacturing method
CN112501493A
Method for preventing crack from occuring on hotrolled coil of austenitic stainless steel with highdelta-ferrite
KR1020010047690A